Pharmaceutical innovation, incremental patenting and compulsory licensing - Carlos María Correa (South Centre, 2011)
Despite the decline in the discovery of new chemical entities for pharmaceutical use, there is a significant proliferation of patents on products and processes that cover minor, incremental innovations. A study conducted in five developing countries - Argentina, Brazil, Colombia, India and South Africa - evidenced a significant proliferation of 'evergreening' pharmaceutical patents that can block generic competition and thereby limit access to medicines. It also found that both the nature of pharmaceutical learning and innovation and the interest of public health are best served in a framework where rigorous standards of inventive step are used to grant patents. The analysis suggests that local firms in developing countries are better supported in a framework where patent protection for minor incremental innovations is not allowed. The study also suggests that with the application of well-defined patentability standards, governments could avoid spending the political capital necessary to grant and sustain compulsory licenses/government use. If patent applications were correctly scrutinized, there would be no need to have recourse to such measures.
Keywords: 300; Pharmakologie; Arzneimittel; Patent; Lizenz; Immaterialgüterrechte; Innovationsdiffusion; Argentinien; Brasilien; Kolumbien; Indien; Südafrika